(untitled) (Colombia Medica, 2008)
Insulin acts on metabolisms and normal growth. In the past decades, its effects on central nervous system functions, such as: appetite-satiety cycle modulation, reproductive function, neurotransmitter release, neuronal survival and synaptic plasticity have been discovered. Evidences got from animal models and neuropathologic findings, have elucidated a fraction of the mechanism that associates insulin signal with neurodegenerative syndromes, like Alzheimer disease. Here, insulin action on hypothalamus, neuron survival, synaptic plasticity and implications of this knowledge on understanding degenerative process of central nervous system particularly Alzheimer disease, will be reviewed.